EFEKTIVITAS MEDIA SOSIAL INSTAGRAM DALAM MEWUJUDKAN PARTISIPASI POLITIK MASYARAKAT : Studi Kasus Akun Instagram Ridwan Kamil terhadap Masyarakat Kota Bandung - Windy Inneke Putri, - (2019)
Social media is something familiar to our community in this new era. In its use, social media that is mostly being used is Instagram. Instagram has targeted various aspects, one of them is politics. The political concept that is familiar to community is political participation. The existence of Instagram is used as a basis for political participation with new media. This is also supported by political actors who have an Instagram account, one of them is Ridwan Kamil. This research was conducted to find out the effectiveness of Instagram social media in realizing community political participation by using qualitative approach and case study method. Data collection is done by interview, observation and documentation study. The results of the study show that: 1) The forms of political participation that can be done on Ridwan Kamil's Instagram account include the form of idea, energy and material. In general, the most dominant form is the form of idea. 2) The obstacles faced are lack of human resources in managing Ridwan Kamil's Instagram account, lack of public manners, and the risk of hoaxes.3) The efforts made to overcome these obstacles are by creating a team in order to follow up on community participation, strengthening education in schools and families and understanding the regulations of hoax. 4) The results obtained are the existence of government work units born from social media such as @jabarquickresponse, @jabarsaberhoax and Ridwan Kamil's Instagram account have effectively achieved the political participation of the community. It can be seen from the full comments column of Ridwan Kamil's Instagram account by community political participation.